MEDIASI PENAL SEBAGAI ALTERNATIF PENYELESAIAN PERKARA PENCURIAN RINGAN DI KEPOLISIAN RESOR KOTA PAYAKUMBUH - Putra, Ryanda; Effendi, Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Minor criminal acts (Tipiring) are minor or non-hazardous criminal offenses that cover minor crimes written in the second book of the Criminal Code which consist of, light animal abuse, light abuse, minor abuse, minor theft, minor embezzlement, minor fraud, light damage and light storage. The Supreme Court has issued a Supreme Court Regulation Number 2 of 2012 concerning the Limitation of Light Crimes (Tipiring) and the Amount of Fines in the Criminal Code. Penal Mediation is an alternative solution to minor crimes.This type of research can be classified in the type of sociological legal research (empirical), because in this study the author immediately conducts research on the location or place under study to provide a complete and clear picture of the problem under study. This research was conducted at the Head of Payakumbuh City Police Investigator section, Payakumbuh City Police Investigator Section and Light Burglary Actors. The data sources used are primary data, and secondary data. Data collection techniques in this study were interviews, questionnaires, and literature review.The conclusion that can be obtained from the results of the research is that the Implementation of Penal Mediation as an alternative solution to the theft of light in the Payakumbuh City Police has been implemented but has not been fully implemented as an alternative solution to minor theft cases. Many considerations from investigators, one of which is a crime that disturbs the public. Although the value of the loss of a crime is very small. The implementation of Penal Mediation has also not been supported by the basis of regulations governing reason mediation so that investigators are still hesitant to implement it. The Penal Mediation implementation has also not been supported by the basis of regulations governing penal mediation so that investigators are still hesitant to implement it. The obstacles faced by Payakumbuh City Police in the implementation of penal mediation consist of constraints of law enforcement officials, legal factors and community factors. Legal factors, namely the provisions concerning the mechanism of investigation, have actually been regulated but there is no regulatory basis governing criminal mediation, especially in light of theft so that investigators are still hesitant to submit all cases of minor theft cases handled and citizens have not fully known and understand the applicable law related to the existence of reasoning mediation as an alternative solution to minor criminal cases.Keywords: Penal Mediation, Alternative Case Settlement, Mild Theft